Effects of black vinegar beverage intake on exercise-induced fatigue in untrained healthy adults: a randomized, double-blind, placebo-controlled trial - Shun Inagaki; Yoshitake Baba; Takayuki Ochi; Yoshie Sakurai; Takanobu Takihara; Yuko M. Sagesaka (Japanese Society of Physical Fitness and Sports Medicine, 2020)
In this study, healthy participants aged 30 to 45 years, who do not exercise regularly, were administered black vinegar beverages (containing acetic acid) daily for 7 days and assessed for feelings of physical fatigue following exercise. The study was a randomized, double-blind, placebo-controlled crossover study. The evaluation was conducted mainly using the Visual Analog Scale (VAS), which assesses feelings of physical fatigue, to measure levels of serum creatine kinase (CK). Feelings of fatigue were determined using the VAS with an ergometer before, immediately, and 30 and 60 min after exercise, as well as at bedtime, and the following morning after awaking. Our results showed that 7 days of test beverage (containing 666 mg acetic acid) intake significantly decreased feelings of physical fatigue 30 min following exercise and at bedtime, compared to intake of the placebo beverage (containing 54.8 mg acetic acid). Furthermore, in the test beverage condition, feelings of shoulder stiffness were significantly decreased at bedtime on the day of exercise and the following morning. However, the test beverage had no significant effects on subjective feelings of fatigue or pain in the leg muscles or levels of serum CK after exercise. Our findings suggested that acetic acid may contribute to a more rapid recovery of physical fatigue after exercise.